Star Wars : shattered empire - Rucka, Greg (Journey to Star wars: the force awakens., 2015)
"Journey ... into the time after the end of Stars Wars: Episode VI 'Return of the Jedi!' [This collection] take[s] us past the destruction of the second Death Star-- and into the chaos of a shattered Empire. Everything you need to know if right here!"--Page 4 of cover.